The long-term assessment of Miscanthus gigantheus cultivation in the Forest-Steppe zone of Ukraine - Kvak, V.; Квак, В.; Stefanovska, T.; Стефановська, Т.; Pidlisnyuk, V.; Підліснюк, В.; Alasmary, Z.; Аласмари, З.; Kharytonov, M.; Харитонов, Микола Миколайович (Національний інститут досліджень - Розробка машин і установок, призначених для сільського господарства та харчової промисловості - INMA Бухарест, 2018)
Multi-year results of research of Miscanthus x giganteus cultivation in several parts of Ukrainian Forest-Steppe zone: western, central, and left parts are presented. The weather conditions at four research sites, based on the meteorological data for years 2011-2015 were analysed. Two subzones of unstable and insufficient rainfall distribution were selected. The influence of climatic conditions to Miscanthus x giganteus production was evaluated. The equation of the regression of yield dependence on hydrothermal coefficient and planting density was calculated. It was established that the indexes of environmental conditions in observed climate zones of Ukraine varied from - 0.41 to 0.29 conventional units. The proposed approach provided the opportunity to predict the yield and energy output of Miscanthus x giganteus when the data of planting density are known. Багаторічні результати досліджень вирощування Miscanthus x giganteus в декількох частинах лісостепової зони України: Західної, Центральної і лівої частини. Погодні умови в чотирьох науководослідних стаціонарах, на основі метеорологічних даних на 2011-2015 роки були проаналізовані. Були обрані дві підзони нестійкого та недостатнього розподілу опадів. Вплив кліматичних умов на вирощування Міскантуса х giganteus був оцінений. Рівняння регресії залежності врожайності від гідротермічного коефіцієнта і щільність посадки було розраховано. Було встановлено, що показники екологічної обстановки в спостережуваних кліматичних зонах України коливаються - від 0,41 до 0.29 умовних одиниць. Запропонований підхід надає можливість прогнозувати урожайність і вихід енергії Miscanthus x giganteus, коли відомі дані щільності посадки.
Багаторічна оцінка вирощування miscanthus× gigantheus у лісостеовій зоні України
Keywords: Miscanthus; Міскантус; weather; погода; yield; врожайність; planting density; густота посадки; energy output; енерговитрати; prediction; прогноз